Active commuting to school and physical activity levels among 11 to 16 year-old adolescents from 63 low-and middle-income countries - Peralta, Miguel (2020)
Background: Global physical activity levels are low. Active commuting to school is a low-cost and sustainable behaviour that promotes adolescents’ physical activity levels. Despite its importance, data on low- and middle-income countries is scarce. This study aimed to assess the relationship between active commuting to school and physical activity (PA) levels among 11–16 years-old adolescents from 63 low- and middle-income countries and six world regions. Methods: Data were from the GSHS database. Participants were 187,934 adolescents (89,550 boys), aged 11–16 years-old, from 63 low- and middle-income countries. Active commuting to school and PA were self-reported as the number of days adolescents walked or cycled to school and engaged in physical activity for at least 60 min in the past 7 days. Results: Boys and girls who actively commuted to school presented higher prevalence of attaining the PA recommendations, but only for the 13–14 (boys: 16.6% versus 22.0%; girls: 9.8% versus 14.6%) and 15–16 (boys: 16.3% versus 21.6%; girls: 8.0% versus 14.0%) year-old age groups. Only for Oceania, Central Asian, Middle Eastern, and North African girls and Sub-Saharan African boys no difference was found in the prevalence of attaining the PA recommendations between those who actively commuted to school and those who did not. Boys who actively commuted to school were 42% (95% CI: 1.37, 1.46) more likely to achieve the PA recommendations, while girls were 66% (95% CI: 1.59, 1.73) more likely to achieve the PA recommendations. Conclusions: Active commuting to school is associated with the adolescents’ physical activity levels. However, it may have a lesser influence in helping younger adolescents attaining physical activity recommendations. Public health authorities should promote active commuting to school among adolescents in order to improve the PA levels and promote health.